On Regional Boundary Gradient Strategic Sensors In Diffusion Systems - Al-Saphory, Raheam; Al-Shaya, Ahlam Y (JOURNAL OF ADVANCES IN MATHEMATICS, 2021)
This paper is aimed at investigating and introducing the main results regarding the concept of Regional Boundary Gradient Strategic Sensors (RBGS-sensors the in Diffusion Distributed Parameter Systems (DDP-Systems . Hence, such a method is characterized by Parabolic Differential Equations (PDEs in which the behavior of the dynamic is created by a Semigroup ( of Strongly Continuous type (SCSG in a Hilbert Space (HS) . Additionally , the grantee conditions which ensure the description for such sensors are given respectively to together with the Regional Boundary Gradient Observability (RBG-Observability can be studied and achieved . Finally , the results gotten are applied to different situations with altered sensors positions are undertaken and examined.